Analisis Pengaruh Return on Asset (ROA), Biaya Operasional Terhadap Pendapatan Operasional (BOPO), Suku Bunga, Financing to Deposits Ratio (FDR) dan Non Performing Financing (NPF) Terhadap Tingkat Bagi Hasil Deposito Mudharabah (Studi Empiris pada Bank Um - Nana Novianti; Tenny Badina; Aditia Erlangga (Esensi: Jurnal Bisnis dan Manajemen, 2015)
Level of profit sharing given by Islamic Banks which is one factor public appeal to save funds in the products of Islamic Banks but in level of profit sharing for giving of Islamic Banks still refers to the rate of Conventional Banks. Still referring to Conventional Bank interest rates make people still think that the same Islamic Banks with Conventional Banks. This research purpose to analyze the effect of financial ratios and interest rate to the level of profit sharing of mudharabah deposits Islamic Banks in Indonesia. The population used is the quarterly financial statements throughout Islamic Banks in Indonesia 2011-2013. Selection of the samples tested in this study using purposive sampling method, 6 selected Islamic Banks. Analysis tools in this study is used multiple regression analysis using SPSS 19.0 software. The variables used in this study are Return On Asset (ROA), BOPO, Interest Rate, Financing To Deposits Ratio (FDR) and Non Performing Financing (NPF) as the independent variable, and level of profit sharing mudaraba deposits as the dependent variable. Partial results show that Return On Asset (ROA) and Financing To Deposits Ratio (FDR) significant positive effect on level of profit sharing mudaraba deposits while the BOPO, Interest Rate and Non Performing Financing (NPF) have no effect.DOI: 10.15408/ess.v5i1.2333